KURIKULUM MERDEKA AND TRANSFORMATION OF LEARNING TOOLS IN EARLY CHILDHOOD EDUCATION - Rantina, Mahyumi (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2024)
This research was conducted with the aim of knowing the transformation of learning tools in the independent curriculum carried out by PAUD educators. This type of research is descriptive quantitative with a survey research design and data collection techniques in the form of filling out a questionnaire via Google Form. The sample in this study was PAUD educators with the number of respondents in this study being 71 respondents and carried out from May-June 2024. From the research findings, the independent curriculum has been dominantly used in educational units, but its implementation is due to the transformation of various components of learning tools such as names, components, learning objectives, assessment learning outcomes so that there are still many educators who have difficulty in compiling learning tools used in the learning process, educators find difficulties in compiling the flow of learning objectives, determining learning outcomes and compiling project-based teaching modules for Pancasila students. So educators need a variety of examples, application of good practices, and training activities, workshops on preparing learning tools that are in accordance with the independent curriculum